Effect of Al2O3 on the Melting, Viscosity, and Phosphorus Distribution of CaO–SiO2–Fe2O3–P2O5 Slag System. Issue 7 (29th May 2018) - Xie, Senlin; Wang, Wanlin; Pan, Zihang; Li, Hongchao; Huang, Daoyuan; Du, Yong
Abstract : An investigation is conducted to study the effect of Al2O3 on the melting, viscosity, and phosphorus distribution of CaO–SiO2–Fe2O3–P2 O5 slag system by using Single Hot Thermocouple Technique and rotating cylinder viscometer. The results show that with the addition of Al2 O3 content, the melting temperature range of slag system is first reduced and then increased, as the added Al2 O3 may react with CaO to form different compounds with varied melting points. The slag viscosity increases with the addition of Al2 O3 content, due to the fact that the polymerization degree of the melt slag is getting increased. Besides, the addition of Al2 O3 can improve the mass percentage of P2 O5 in the solid phase, but it may reduce the dephosphorization capacity of the slag due to the reduction of the total solid phase solution (2CaO · SiO2 –n3CaO · P2 O5 ) precipitation. The results of this study can elucidate the effect of Al2 O3 on the property of dephosphorization slag and provide guidelines for the new slag design to achieve a better hot metal dephosphorization efficiency. Abstract : With the addition of Al2 O3 in the CaO–SiO2 –Fe2 O3 –P2 O5 slag, the melting temperature range is first reduced and then increased; the viscosity is increased. Besides, it is found that the addition of Al2 O3 can improve the mass percentage of P2 O5 in the solid phase, but it will reduce the dephosphorization capacity of the slag. It can provide guidelines for the new slag design.